2017
DOI: 10.1016/j.geomphys.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Poisson cohomology of scalar multidimensional Dubrovin–Novikov brackets

Abstract: Abstract. We compute the Poisson cohomology of a scalar Poisson bracket of Dubrovin-Novikov type with D independent variables. We find that the second and third cohomology groups are generically nonvanishing in D > 1. Hence, in contrast with the D = 1 case, the deformation theory in the multivariable case is non-trivial.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(43 citation statements)
references
References 19 publications
0
35
0
8
Order By: Relevance
“…Very recently it has been proved that the Poisson cohomology of multidimensional scalar brackets is extremely large [3], hence there are plenty of deformations of such structures. The bracket (23) is at the crossroads of the aforementioned cases.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently it has been proved that the Poisson cohomology of multidimensional scalar brackets is extremely large [3], hence there are plenty of deformations of such structures. The bracket (23) is at the crossroads of the aforementioned cases.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the Poisson cohomology for the stretched operator has a striking resemblance to the Poisson cohomology of constant higher order scalar differential Hamiltonian operators. In [2,Remark 15] the Poisson cohomology for the first order scalar differential operator is obtained with a similar approach to the one adopted in this paper. The procedure can be repeated for higher order differential operators of the form Q k (∂) = ∂ 2k+1 .…”
Section: The Poisson Cohomology For Stretched Hamiltonian Operatorsmentioning
confidence: 99%
“…The scalar differential case depending on several independent variables has been addressed in [2,3]: in this case the Poisson cohomology is infinitedimensional, however its highly non-trivial third group imposes enough constraints to classify all the compatible Hamiltonian operators up to an arbitrary order. A natural extension from the continuous to the discrete setting is to study differential-difference systems.…”
mentioning
confidence: 99%
“…While the results already obtained by the author for two-component two-dimensional brackets of hydrodynamic type [6] did not allow to conclude anything about the triviality of the dispersive deformations of the bracket, they already showed that the first cohomology group is not vanishing in the second degree, as opposite as Getzler's result. Moreover, a careful study of one-component, two-dimensional brackets [4] tells that the cohomology groups (H ≥1 ) are infinite dimensional, in particular revealing the normal form of the finite Poisson brackets of arbitrary differential order [3].…”
Section: Cohomology Of a Pva And The Theory Of Deformationsmentioning
confidence: 99%
“…We can compare it with the dimension of the cohomology groups for the scalar two-dimensional bracket {u λ u} (sc) = λ y computed in [4] for general values of (p, d). We get…”
Section: Further Remarks On H P D (P 1 )mentioning
confidence: 99%